1999
DOI: 10.1007/s002400050130
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization during volume reduction of solutions with a composition corresponding to that in the collecting duct: the influence of hydroxyapatite seed crystals and urinary macromolecules

Abstract: To examine the effect of hydroxyapatite (HAP) seed crystals and urinary macromolecules on the crystallization under conditions similar to those in the collecting duct (CD), we evaporated 100 ml samples of salt solutions with an ioncomposition assumed to correspond to that in the CD without and with HAP seed crystals. The crystallization in seeded solutions was assessed both with and without dialyzed urine (dU). After evaporation, the number and volume of crystals were recorded and the crystal morphology was ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 41 publications
2
4
0
Order By: Relevance
“…The present results indicate that CaP formed above the CD, whether in the proximal tubule (1), in the loop of Henle (3,5) or in the distal tubule (1, 2), might induce a heterogeneous nucleation of CaOx in CD urine at pH levels below 6.2. This is in accordance with our previous results (7)(8)(9).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…The present results indicate that CaP formed above the CD, whether in the proximal tubule (1), in the loop of Henle (3,5) or in the distal tubule (1, 2), might induce a heterogeneous nucleation of CaOx in CD urine at pH levels below 6.2. This is in accordance with our previous results (7)(8)(9).…”
Section: Discussionsupporting
confidence: 94%
“…We have shown previously that CaP is the favoured crystallization product at nephron levels above the CD, and that CaOx forms more easily lower in the nephron (1,2,7,26). The present results indicate that CaP formed above the CD, whether in the proximal tubule (1), in the loop of Henle (3,5) or in the distal tubule (1, 2), might induce a heterogeneous nucleation of CaOx in CD urine at pH levels below 6.2.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Several previous studies have shown that CaOx crystals can easily form inside distal renal tubules and urine pH is a crucial factor affecting such crystallization 2427 . The difference of urine pH could generate various CaOx crystal types 14 .…”
Section: Resultsmentioning
confidence: 99%